New Integrated Model Approach to Understand the Factors That Drive Electronic Health Record Portal Adoption - Tavares, Jorge (2018)
Tavares, J., & Oliveira, T. (2018). New Integrated Model Approach to Understand the Factors That Drive Electronic Health Record Portal Adoption: Cross-Sectional National Survey. Journal Of Medical Internet Research, 20(11), [e11032]. DOI: 10.2196/11032